Development of Single Nucleotide Polymorphism (SNP) Markers in Tropical Crops - Dwiningsih, Yheni; Rahmaningsih, Miranti; Alkahtani, Jawaher (Advance Sustainable Science, Engineering and Technology, 2020)
Understanding genetic diversity, association studies, evolution analysis, quantitative trait loci, marker-assisted selection and genome-wide association in tropical crops are important for improving plant characteristics in order to increase food sustainability in tropical countries. Single nucleotide polymorphism (SNP) marker is becoming the most popular molecular marker for those studies. By using SNP marker, genes associated with important traits can be identified efficiently compared to the other molecular markers. This review describes about how SNP can be discovered in the plant genomes and the application of SNP in plant breeding, especially in tropical crops such as rice, maize, peas, potato, tomato, cassava, taro, etc. Â Â Keywords: food sustainability, plant breeding, SNP marker, tropical crops